The Role of Business Intelligence in Achieving Healthcare Quality in Neonatal Surgery - Adlane, Brahimi; Sarra, Redjimi; Chabane, Guessabi; Yassine, Sakhaf (Journal of Neonatal Surgery, 2025)
This article examines the role of Business Intelligence (BI) systems in improving healthcare quality within neonatal surgery units. It highlights how BI supports data-driven decision-making through the integration, analysis, and visualization of large volumes of clinical and operational data. The study emphasizes the contribution of BI systems to monitoring key performance indicators, enhancing surgical outcomes, reducing complications and infections, and improving patient safety and parental satisfaction. It also discusses the technical, administrative, and ethical challenges associated with BI implementation in neonatal healthcare settings. Furthermore, the article explores the integration of BI with advanced technologies such as artificial intelligence, predictive analytics, smart monitoring systems, and digital healthcare applications. The findings suggest that effective adoption of BI systems can significantly enhance healthcare quality, operational efficiency, and strategic planning in neonatal surgery, provided that appropriate technological infrastructure, skilled human resources, and organizational support are ensured.